PENERAPAN POJOK BACA DI KELAS DALAM MENDUKUNG BUDAYA LITERASI DI SEKOLAH DASAR - Latifatun Nadya; Yulina Ismiyanti; Sari Yustiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on research conducted by the Program for International Student Assessment (PISA), students in Indonesia are ranked 57th out of 65 countries studied in terms of reading ability. The culture of literacy in Indonesia is said to be declining. The causal factor is the low interest in reading among students. The implementation of a culture of literacy in elementary schools is very important to build a strong foundation of reading skills in students. One effective strategy in developing a culture of literacy is to create a reading corner in the school environment. A reading corner is a special area designed to encourage students to be more interested in reading by providing various types of reading that suit their interests and age. This study aims to determine the literacy program in schools in developing reading habits, especially through reading corners for students in elementary schools. The research method used is library research. The results of the study on the implementation of reading corners in elementary schools have an important role in supporting a culture of literacy among students. Reading corners provide easier access to reading materials, increase interest in reading, and build literacy habits from an early age. In addition, mentoring strategies from teachers and a supportive environment also contribute to creating a pleasant reading experience.